(untitled) (Rabi Sangyan, 2024)
This research investigates the impact of service marketing factors on customer satisfaction and loyalty within the Nepalese tourism industry, focusing on service quality, price competitiveness, location accessibility, cultural experiences, and brand image. A diverse sample of 185 respondents was analyzed, revealing a near-even gender distribution predominantly from the 26-35 and 36-45 age groups. The descriptive analysis indicated that while service quality is generally perceived positively, improvements are needed in pre-trip information provision. Price competitiveness was identified as a strong asset, but enhancing pricing transparency could further strengthen this factor. Respondents expressed positive feedback regarding location accessibility and cultural experiences, although concerns about the authenticity of cultural performances emerged. Correlation and regression analyses demonstrated significant relationships between service quality, price competitiveness, location accessibility, cultural experiences, brand image, and customer satisfaction. Notably, price competitiveness and location accessibility were robust predictors of satisfaction. The findings underscore the multifaceted nature of service marketing in Eastern Nepal’s tourism sector and provide actionable recommendations for stakeholders to enhance tourist experiences and promote sustainable growth in the industry. Continuous adaptation of marketing strategies is essential to maintain competitiveness in the evolving tourism landscape.